2021
DOI: 10.1101/2021.02.03.21250974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of individual and ensemble probabilistic forecasts of COVID-19 mortality in the US

Abstract: Short-term probabilistic forecasts of the trajectory of the COVID-19 pandemic in the United States have served as a visible and important communication channel between the scientific modeling community and both the general public and decision-makers. Forecasting models provide specific, quantitative, and evaluable predictions that inform short-term decisions such as healthcare staffing needs, school closures, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…We found that the mean-ensemble model made the most accurate (as measured by median rWIS) and most consistently accurate (as measured by rWIS IQR) forecasts across forecast horizons, forecast dates and Trusts, overcoming the variable performance of the individual models. This is consistent with other COVID-19 forecast evaluation studies [8,14,21,23] and other diseases [25,27,48].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that the mean-ensemble model made the most accurate (as measured by median rWIS) and most consistently accurate (as measured by rWIS IQR) forecasts across forecast horizons, forecast dates and Trusts, overcoming the variable performance of the individual models. This is consistent with other COVID-19 forecast evaluation studies [8,14,21,23] and other diseases [25,27,48].…”
Section: Discussionsupporting
confidence: 92%
“…This paper systematically evaluates the probabilistic accuracy of individual and ensemble real-time forecasts of Trust-level COVID-19 hospital admissions in England between September 2020 and April 2021. Whilst other COVID-19 forecasting studies evaluate forecasts at the national or regional level [8,21,22], or for small number of local areas (e.g. the city of Austin, TX, USA [9]; the five health regions of New Mexico, USA [10]; or University College Hospital, London, UK [11], this work evaluates forecast performance over a large number of locations and forecast dates and explores the usage of aggregate case counts as a predictor of hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As was mentioned earlier, ensemble forecasts have also been used in a variety of other applications in real-time forecasting of infectious diseases, often with seasonal transmission dynamics where many years of training data are available (Yamana et al, 2016;Reich et al, 2019;Reis et al, 2019;Colón-González et al, 2021). In such applications, simple combination approaches have generally been favored over complex ones, with equal-weighted approaches often performing similarly to trained approaches that assign weights to different models based on past performance Bracher et al, b). These results align with theory suggesting that the uncertainty in weight estimation can pose a challenge in applications with a low signal-to-noise ratio (Claeskens et al, 2016).…”
Section: Related Literaturementioning
confidence: 99%